Factors affecting the implementation of occupational therapy home programmes for children with learning difficulties in Gauteng - Joshi, Shruti (My University, 2020)
The purpose of the study was to determine what parents of children with learning difficulties, attending mainstream schools and who access private occupational therapy services, in Gauteng, consider to be factors affecting the implementation of home programmes. Paediatric occupational therapists use home programmes as a part of treatment, to enhance therapeutic outcomes and sometimes as a substitute for therapy. The study used a quantitative descriptive cross-sectional survey design, and a convenient sample was sourced from 88 occupational therapy private practices in Gauteng. A survey questionnaire was compiled, based on literature, and piloted for content validity. This was distributed electronically using RedCap. Seventy nine questionnaires were returned and analysed. The results indicated that the parents were mostly responsible for the implementation of the home programme. Most participants ascribed moderate to maximal importance to their children’s home programmes and were willing to implement the home programme a few times a week for 15 minutes or less. Very few parents were involved in the design of the programme and programme goals and the therapist seldom based the programme on a home visit. The greatest barrier to implementation of home programmes was lack of time, with other barriers being child fatigue or overstimulation, family factors, lack of resources and poor programme content. Facilitators to home programme implementation included specific and easy to follow exercises/activities, collaborative goal setting, inclusion of the family in the activities, incorporating the programme into daily routine, and regular communication with the therapist. Parents suggested that changes such as providing carefully selected programme activities and therapist guidance would most improve implementation of home programmes The factors influencing home programme implementation, experienced by South African parents in Gauteng, are similar to those identified in other studies and texts. The study also identified deficits in the occupational therapists’ process of designing and monitoring home programmes, which has implications for clinical practice and parents adherence to home programmes
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Occupational Therapy, 2020